2022
DOI: 10.1038/s41598-021-04004-1
|View full text |Cite
|
Sign up to set email alerts
|

A scoring system combining clinical, radiological, and histopathological examinations for differential diagnosis between lipoma and atypical lipomatous tumor/well-differentiated liposarcoma

Abstract: This study evaluated the diagnostic accuracy of clinical, radiological, and histopathological examinations for differential diagnosis between atypical lipomatous tumor (ALT)/well-differentiated liposarcoma (WDLS) and lipoma, and aimed to develop a new combined scoring system for the preoperative diagnosis of ALT/WDLS. Eighty-nine lipomas and 56 ALT/WDLS were included and their clinical characteristics, magnetic resonance imaging (MRI) findings, histological findings by hematoxylin and eosin (HE) staining were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…Lipomas are discrete, encapsulated, homogeneous fatty masses on CT and MRI. On the other hand, thickened or nodular septa (>2 mm), prominent foci of high T2 signal and prominent areas of enhancement on MRI have been reported to be features suspicious of liposarcoma [ 5 , 6 ]. In addition, tumor size >10 cm and fat content <75% have been reported as radiological features of liposarcoma [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipomas are discrete, encapsulated, homogeneous fatty masses on CT and MRI. On the other hand, thickened or nodular septa (>2 mm), prominent foci of high T2 signal and prominent areas of enhancement on MRI have been reported to be features suspicious of liposarcoma [ 5 , 6 ]. In addition, tumor size >10 cm and fat content <75% have been reported as radiological features of liposarcoma [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, thickened or nodular septa (>2 mm), prominent foci of high T2 signal and prominent areas of enhancement on MRI have been reported to be features suspicious of liposarcoma [ 5 , 6 ]. In addition, tumor size >10 cm and fat content <75% have been reported as radiological features of liposarcoma [ 6 ]. SUVmax of FDG-PET reported that lipomas measured 0.8 ± 0.2 and well-differentiated liposarcomas measured 2.3 ± 1.2 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALT and WDLS, which are locally aggressive tumors, are often grouped together in the literature and referred to synonymously since they are identical morphologically, only differing by tumor location [12 , 13] . ALTs are in areas accessible for surgical resection such as the trunk and extremities, where tumors in regions that cannot be resected such as the retroperitoneum, are termed WDLS [12 , 13] . Both ALT and WDLS are considered low-grade malignancies as they are not known to cause distant metastases, as their aggressive liposarcoma counterpart [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Both ALT and WDLS are considered low-grade malignancies as they are not known to cause distant metastases, as their aggressive liposarcoma counterpart [12] . However, surgical resection is still important to confirm pathology, to eliminate the potential for de-differentiation, although rare especially in the superficial locations, and to minimize persistent local advancement of disease [13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation